ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FUNGSI KONSUMSI MASYARARAT DI PROPINSI JAWA TENGAH PADA TAHUN 2000 - Nurhayati, Siti Fatimah; Rachman, Masagus (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
Household consumption is the biggest expense component in Gross Domestic Product every year. There are many economic factors theoretically contribute to the number of expense percentage. In this research the writer studies three economic factors in Central Java Province which are regarded to have significant influences on the household consumption rate, namely; income rate, population number, inflation rate.This research uses regression econometric analyses means of ordinary Least Square (OLS) with cross section secondary data input in 2000 taken from statistical center body.